Proximity of the roots of maxillary posterior teeth to the floor of maxillary sinus and cortical plate: A cone-beam computed tomography assessment - Shikha N Goyal; Freny R Karjodkar; Kaustubh Sansare; Mohd Saalim; Sneha Sharma (Wolters Kluwer Medknow Publications, 2020)
Introduction: The purpose of the study is to assess the vertical and horizontal relationship between the roots of maxillary posterior teeth and neighboring structures like the floor of the maxillary sinus and cortical plates using cone-beam computed tomography (CBCT). Method and Materials: 100 CBCT scans of the patients from the Indian population were analyzed. Vertical and horizontal relationship between the roots of maxillary posterior teeth and the floor of the maxillary sinus was divided into 4 types and 3 types, respectively. Distances between the root apices and the floor of the maxillary sinus and cortical plate was measured for each root and results were formulated. Results: In total 365 teeth were assessed, 185 first molar and 180 second molar. It was found that the roots of first molar and second molar usually had type 2 (root apices in close contact with the floor of maxillary sinus) and type 3 (roots projecting laterally into the sinus, but its apices are outside the sinus border) vertical relationship respectively with the floor of maxillary sinus. The deepest portion of the floor of the maxillary sinus was most commonly seen projecting between buccal and palatal roots. The mean distance between the cortical plate and root was highest for the distobuccal root of second molar i.e., 1.20 mm SD = 0.97. Conclusion: The distobuccal root of the first molar and mesiobuccal root of the second molar are closest to the sinus floor, hence clinician should be extra cautious while working on these roots during endodontic or surgical procedures in the Indian population.